The Signature Program: Bringing the Protocol to the Patient. Issue 2 (11th May 2015) - Kang, BP; Slosberg, E; Snodgrass, S; Lebedinsky, C; Berry, DA; Corless, CL; Stein, S; Salvado, A
<x xml:space="preserve">Abstract</x> Early‐phase clinical development in oncology has evolved dramatically with the deciphering of the human genome in 2004. Genomic analysis and the tools identifying genetically disrupted pathways within a patient's tumor have been a driving force for personalized medicine and for the development of highly targeted novel therapies. Tumors are often genetically heterogeneous, with multiple concurrent genetic abnormalities. On the other hand, tumors arising from different tissues may share identical molecular drivers.